FAKTOR-FAKTOR YANG BERPENGARUH TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN MANUFAKTUR DI INDONESIA - CHRISTIANTO CHANDRA; NELLIYANA NELLIYANA (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2021)
The purpose of study is to obtain an empirical evidence about the influence of independent variables on firm value. These independent variables are managerial ownership, independent board of commissioner, audit committee, firm size, return on equity, ownership concentration, and institutional ownership. The population used in this research are manufacturing companies list on Indonesian Stock Exchange from 2012-2015, where are 60 companies selected as final sample. The hypothesis in this study is tested by using multiple regression analysis. The result of this research shows that independent board of commissioner, firm size, and return on equity have positive influence on firm value, while managerial ownership, audit committee, ownership concentration, and institutional ownership did not have influence on firm value